Morphological and Functional Outcomes after Intravitreal Dexamethasone Injection for Macular Edema in Patients with Central Vein Occlusion at 48-Week Follow-Up. (11th February 2020) - Nicula, Cristina; Nicula, Dorin; Rednik, Anca; Bulboaca, Adriana; Crișan, Ovidiu
Abstract : Purpose . The purpose of the study was to assess the efficacy of intravitreal dexamethasone implant (IDI: Ozurdex®) injection in eyes with macular edema due to retinal vein occlusion. Material and Method . A retrospective, nonrandomized study was conducted in patients with macular edema (ME) due to retinal vein occlusion (RVO) who undertook intravitreal Ozurdex® as first-line treatment. We performed a complete ocular exam including macular OCT. Results . The mean BCVA (logMar) improved from 0.420.42 ± 0.23 logMar at baseline to 0.21 ± 0.23 logMar at 48 weeks in the BRVO group and from 0.72 ± 0.16 logMar at baseline to 0.31 ± 0.23 logMar at 48 weeks in the CRVO group. In both groups, CFT values decreased significantly compared to baseline (p < 0.0001 at each timepoint). Reinjection for recurrent macular edema after 18 weeks was indicated in five eyes (41.67%) in the BRVO group and in six eyes (25%) in the CRVO group. Cataract developed in two eyes (16.67%) in the BRVO group and in one eye (4.17%) in the CRVO group. The IOP was higher than 25 mmHg in two cases in the BRVO group (16.66%) and in three cases (8.33%) in the CRVO group. Conclusion . Ozurdex® injected intravitreally significantly improved the mean CFT and BCVA in eyes with macular edema due to retinal vein occlusion.